Kontribusi Pemikiran Islam terhadap Isu Kontemporer: Modernitas, Globalisasi, dan Keberlanjutan Lingkungan: The Contribution of Islamic Thought to Contemporary Issues: Modernity, Globalization, and Environmental Sustainability - Retna Dwi Estuningtyas; Ahmad Syaefuddin (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This article examines the contributions of Islamic thought in responding to three interrelated contemporary issues: modernity, globalization, and environmental sustainability. Employing an integrative library research approach drawing on recent primary and secondary sources (2020–2025), this study demonstrates that the Islamic epistemological framework—grounded in maqāṣid al-sharīʿah, the concept of khilāfah, and fiqh al-bīʾah—offers normative solutions that are both relevant and complementary to global sustainable development discourse. Key findings indicate that: (1) contemporary Islamic thought successfully dialogues between classical Islamic intellectual tradition and the demands of modernity without compromising theological integrity; (2) Islamic universalism provides a robust ethical foundation for responding to the disruptions of globalization; and (3) Qur'anic principles of mīzān and nahy 'an al-fasād bear direct relevance to the 2030 Sustainable Development Goals (SDGs). This research contributes to the academic discourse of Islamic studies and global environmental studies, while providing a value-based Islamic policy framework.